Internet of Things (IoT) Based Speed Monitoring System for Electric Cars - Putra, Rean Andhika; Ma’arif , Alfian (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
The electric cars that have been made are also being competed at national events such as the FESC IIMS 2022 event in Jakarta and the Inter-College Electric Car Joint Training by the Ministry of Public Works and Public Housing (PUPR) in the context of the 2022 Road Day and the Indonesian Electric Car Contest (KMLI) at the Bandung State Polytechnic in Bandung until now. For the sustainability of electric cars, various research still needs to be carried out to achieve optimal electrical system design. Here, Ahmad Dahlan University's electric cars can operate at speeds above 30,000 rpm when monitored using a speedometer, but here there is no design for a long-distance speed monitoring system, therefore team colleagues who are in the paddock during the competition are not yet able to monitor the speed from inside the paddock. This system needs to be used during the race so that team mates in the paddock during the race can also monitor the speed of the Electric Car during the race when the race starts. This system is used using the Internet of Things (IoT) method because IoT can display speed data via a laptop and can implement a remote monitoring system. Therefore, in this final report, we will discuss how to design and implement a speed monitoring system for electric cars based on the Internet of Things (IoT). To get the best results and as expected, the design of this system refers to various sources. Where the input component is the detection from the Optocoupler Sensor after detecting the wheel speed, then the data is processed via Arduino using program initiation on the Arduino ide, after that the output will be generated on the I2C LCD and also the output will be displayed on IoT Things Speak because IoT itself, you have to use an internet signal, so here we add the sim800l component which is used to send Arduino data to Thingspeak via the sim800l internet intermediary. This tool was created with the aim of ensuring that the Al-Qorni UAD electric car continues to develop and has an advanced technological system.